ESP32 Real-Time Smoke Detection Integrated with WhatsApp in Tamansari, Karawang - Nurdiyanto, Furkhon; Hafid, Izzul; Nurhayati, Syifa Silvia; Fadilah, Syarifah Nur; Saragih, Yuliarman (Teknik Elektro Universitas Siliwangi, 2025)
This research develops an air quality monitoring system based on the ESP32 microcontroller, utilizing an MQ2 gas sensor and a DHT22 temperature-humidity sensor. The system is designed to monitor gas concentration and environmental conditions (temperature and humidity) in real-time in Tamansari Village, an area known for frequent open burning activities. Sensor readings are periodically transmitted to users via WhatsApp notifications using the CallMeBot API, providing early warnings when potentially hazardous gas levels are detected. Test results indicate that the system effectively detects changes in gas concentrations and temperature with reasonable accuracy and delivers timely alerts. Thus, the system can function as a supportive tool in mitigating air pollution risks in the study area.